Residential housing construction in the film propaganda of the Polish People’s Republic (PRL) - Skotarczak, Dorota (Studia Historiae Oeconomicae, 2025)
Housing construction in the PRL was treated as a priority investment, reflected in media coverage. Showing new “bright” houses and flats had a dimension of propaganda, especially compared to the “dull and damp” ones from before the war. This was a measure of success and modernity. Simultaneously, the current housing policy was promoted in the media, showing its qualities and successes. There was a focus on mass housing, and housing estates, which is reflected in the materials presented here. In the 1970s, the pinnacle of modernity and resilience came from blocks of flats built of large prefabricated concrete slabs, whose production ultimately changed the urban landscape. It was not until after December 1981 that the promotion of housing as one of the major investment successes ceased. Thus, the materials presented here are more of a testimony to its failure. Although, on the other hand, they are also a testimony to the changes taking place: criticism of the big plate, decentralization, and promotion of small, local construction companies.